Edible Bird’s Nest: Recent Updates and Industry Insights Based On Laboratory Findings - Chok, Kian Chung; Ng, Ming Guan; Ng, Khuen Yen; Koh, Rhun Yian; Tiong, Yee Lian; Chye, Soi Moi (Frontiers in Pharmacology, 2021)
Edible bird’s nest is the traditional Chinese delicacy made of the saliva of swiftlets found in Southeast Asia. With the ever-growing demand for EBN, quality control of EBN products is necessary for safety consumption with scientific evidence of beneficial functions for health. The processing steps are particularly important for the efficient extraction of bioactive compounds. Geographical location, collection place, and harvesting season contribute to differences in nutritional contents in EBN. The concern of adulterant, chemical, and microbial contaminants in EBN as well as the authentication and measuring methods are discussed in this review. The recent discoveries of beneficial health functions of EBN in antimicrobial and antiviral actions, immunomodulation, cancer prevention and treatment, tissue regeneration, cardiometabolic maintenance, antioxidant action and neuroprotection are reviewed. Our review provides an update on the recent research on EBN.